Estradiol and Leptin in Women with Obesity, Overweight, and Normal Body Weight - Fitri, Yulia; Tann, Gino; -, Rusdiana (Indonesian Journal of Medicine, 2017)
Background: Prevalence of obesity on women was higher than men. Obesity was related to the resistance of leptin hormone. Estradio hormone also played an important role in energyÃÂ  metabolism and body weight control. The study aimed to discover the relationship between estradiolÃÂ  concentration with leptin concentration on women with obesity, overweight and normal body weight in Banda Aceh City.Subjects and Method: ÃÂ The study was an analytic observational study with case control design. There were a total of 75 women of 20-40 year- old who were selected as research subjects by using purposive sampling. The research subjects were divided into 3 groups, namely obesity, over weight, and normal body weight. The study was conducted in Banda Aceh City in July Ã¢â¬â October 2014. ÃÂ Dependent variable of the study was womenÃ¢â¬â¢s body weight. Independent variables were leptin concentration which was investigated by using ELISA technique and estradiol concentration which was investigated by using AxSYM Estradiol Assay. The data was analyzed by using Spearman correlation test.Results: The result of the study obtained the median value of estradiol concentration on normal group was higher than on obesity and overweight group, that was 63 Pg/mL (18-420). The average concentration of leptin on normal group is higher than obesity and overweight group, that was 4.56 ng/mL (up to ÃÂ± 3.48). However, it did not find any correlation between the concentration of ÃÂ estradiol and the concentration of leptin on women with obesity, overweight and normal weight (R= 0.03; p= 0.121;).Conclusion: The study showed that women with obesity experienced the decreasing concentration of estradiol and leptin, however it did not find significant correlation between estradiol and leptin.Keywords:ÃÂ  estradiol, leptin, women with obesity, overweight, normal body weightCorrespondence:ÃÂ Yulia Fitri. Health Polytechnic, Poltekkes of Aceh, Banda Aceh.Indonesian Journal of Medicine (2017), 2(1): 36-41https://doi.org/10.26911/theijmed.2017.02.01.04